(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
GeoGebra is a widely used dynamic editing software in learning mathematics. This program utilizes visual effects and animations to facilitate the understanding of various mathematical concepts, allowing for the manipulation of graphs and shapes through animation. Through animations, students are able to visualize themselves and learn to connect between mathematical principles. Such visual impact enhances students’ ability to comprehend mathematical sciences among them, aiding both practical and conceptual understanding. In this article, we explore the effectiveness and impact of utilizing GeoGebra animations in the teaching and learning of mathematics for students and educators